The 2003 Eleanor Clarke Slagle lecture. Chaotic Occupational Therapy: collective wisdom for a complex profession. - Royeen CB (American Journal of Occupational Therapy)
In the tradition of Mosey's (1985) Eleanor Clarke Slagle lecture (p. 504) as a road map to where this presentation is going, I will present a short preface and first, talk about her story and our professional identity; second, use chaos theory as a way to look at occupation; third, introduce you to Charlotte's Web of Chaos; fourth, make some conclusions about chaos and occupational therapy; fifth, do an ending to this telling, and; sixth, do a summary and closing.